(untitled) (Journal of Economic Research & Business Administration, 2016)
Nowadays growing of the world population food provision today, becoming one of the most pressing issues. The development of agriculture will increase food security of population, diversify exports in terms of low prices for oil, gas and other natural resources; will reduce inflation in the market, improve the condition of the financial and monetary system. In this regard, it is important to diversify the agricultural sector and the definition of the direction of development, increasing productivity and competiveness of the sector based on innovative technologies. In our country there are all the economic and climatic conditions to ensure an environmentally friendly and high-quality food. Therefore, the development of agriculture should be considered as a package. This article contains a statistical analysis of the issues of agricultural industry with the framework of food security, proposed scientific and innovative methods to improve performance, consider mechanisms to support the domestic market and export directions to foreign markets.